Orai-IGFBP3 signaling complex regulates high-glucose exposure-induced increased proliferation, permeability, and migration of human coronary artery endothelial cells. Issue 1 (21st October 2020) - Bai, Suwen; Wei, Yuan; Hou, Wenxuan; Yao, YanHeng; Zhu, Junwei; Hu, Xianyu; Chen, Wei; Du, Yinan; He, Wei; Shen, Bing; Du, Juan
Abstract : Introduction: Diabetes-associated endothelium dysfunction might be linked to disturbances in Ca 2+ homeostasis. Our main objective is to reveal the potential mechanisms by which high-glucose (HG) exposure promotes increased proliferation of human coronary artery endothelial cells (HCAECs) in culture, and that store-operated Ca 2+ entry (SOCE) and insulin-like growth factor binding protein 3 (IGFBP3) contribute to this proliferation. Research design and methods: We detected the expression levels of Ca 2+ release-activated calcium channel proteins (Orais), IGFBP3 and proliferating cell nuclear antigen of HCAECs cultured in HG medium for 1, 3, 7, and 14 days and in streptozotocin-induced diabetic mouse coronary endothelial cells. Coimmunoprecipitation and immunofluorescence technologies were used to detect the interactions between Orais and IGFBP3 of HCAECs exposed to HG environment, and to detect IGFBP3 expression and proliferation after treatment of HCAECs cultured in HG medium with an agonist or inhibitor of SOCE. Similarly, after transfection of specific small interfering RNA to knock down IGFBP3 protein expression, SOCE activity and Orais expression were tested. Some processes related to endothelial dysfunction, such as migration, barrier function and adhesion marker expression, are also measured. Results: HG exposure promoted increased proliferation of HCAECs in culture and that SOCE and IGFBP3 contributed to this proliferation. In addition, we also found that Orais and IGFBP3 were physically associated and regulated each other's expression levels. Besides, their expression levels and interactions were enhanced in HCAECs after exposure to HG. HG exposure promotes cell migration, but reduces barrier function and adherens junction protein expression levels in HCAECs. Conclusion: Orais and IGFBP3 formed a signaling complex that mediated HCAEC proliferation during HG exposure in culture. Meanwhile, we also found that SOCE stimulates proliferation of HCAECs by regulating IGFBP3, thereby promoting the occurrence and progression of coronary atherosclerosis in diabetes. It is worth noting that our findings may shed new light on the mechanisms of increased proliferation in HCAECs in diabetes and suggest the potential value of SOCE and IGFBP3 as therapeutic targets for coronary atherosclerosis in individuals with diabetes.